2009
DOI: 10.1080/10599240802612539
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Back Pain and Associated Work and Non-Work Variables Among Farmworkers from Starr County, Texas

Abstract: The role of work exposures, depressive symptoms, and sleep in chronic back pain among farmworkers warrants further examination. Refinements in outcome and exposure assessments are also needed given the lack of a standardized case definition and the variety of tasks and crops involved in farm work in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 26 publications
1
37
1
Order By: Relevance
“…Migration places farmworkers in a precarious position, 64 and chronic back pain occurs while migrating. 65 The jobs of immigrant laborers, such as poultry processing workers, involve minimal decision-making and control, leaving them in precarious positions with their employers, coping with leg pain from long hours of standing. 11,66,67 PACE4 farmworkers and non-farmworker manual laborers did not differ significantly in their levels of perceived precariousness.…”
Section: Discussionmentioning
confidence: 99%
“…Migration places farmworkers in a precarious position, 64 and chronic back pain occurs while migrating. 65 The jobs of immigrant laborers, such as poultry processing workers, involve minimal decision-making and control, leaving them in precarious positions with their employers, coping with leg pain from long hours of standing. 11,66,67 PACE4 farmworkers and non-farmworker manual laborers did not differ significantly in their levels of perceived precariousness.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have noted that approximately 20% of Latino farmworkers in Starr County, Texas experienced fairly bad or very bad sleep quality. 26 They also found that Latino migrant farmworkers who indicated that they had experienced poor sleep quality or were depressed were at increased risk of experiencing chronic back pain. Physically strenuous work, such as that performed by farmworkers, has also been associated with increased likelihood of sleep disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…sprains, strains, fractures and other musculoskeletal injuries [8][9][10][11][12][13], pesticide poisoning [6,10,11,14,15], sunstroke, dehydration [16][17][18], and other work-related injuries [1,7,10,11,[19][20][21][22]. Although little is known about the occupational health challenges of aging MSFW, studies of workers employed in other intensive manual occupations suggest that changes in physiological and cognitive functioning associated with aging can reduce physical work capacity and increase susceptibility to musculoskeletal and other injuries [23][24][25][26][27].…”
mentioning
confidence: 99%